Knowledge map on construction of ceramic tableware design - Wu, Wenchao; Md Yusoff, Irwan Syah; Hj Alli, Hassan; Wang, Heng (AMER & cE-Bs, 2024)
The research analyzed 347 ceramic tableware design papers published in the CNKI database from 2003 to 2023 through CiteSpace, revealing the hotspots and future trends of ceramic tableware design research in the past 20 years. The study employs descriptive statistical Analysis, keyword mapping, and burst detection to emphasize the critical role of metrics in future research. The graphical quantification reveals the research trends in ceramic tableware design, identifies the research gaps, challenges, and opportunities, and provides a firm reference and new ideas for future research..